2021
DOI: 10.3390/ijerph18105245
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Aspects of the Initial Evolution of COVID-19 in Microregion of Uberlândia, Minas Gerais (MG), Brazil

Abstract: COVID-19 is considered by the World Health Organization to be a global public health emergency, which presents regional divergences that affect the epidemiological profile of the disease and are associated with political, economic, social and behavioral aspects. We aimed to analyze the epidemiological characteristics of the disease in the microregion of Uberlândia, Brazil, in order to determine risk factors that contributed to progression of SARS-CoV-2 virus. A cross-sectional study was conducted about micro- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
1
0
0
2
Order By: Relevance
“…A similar pattern also manifested itself among the older patients, but less pronouncedly, possibly due to the prevalent accumulation of comorbidities among individuals in these strata. Our results confirmed the association of aging with the demand for healthcare resources and COVID-19-related deaths reported in different Brazilian states, ( Sousa et al, 2020 , Macedo et al, 2020 , Cobre et al, 2020 , Escosteguy et al, 2020 , Moura et al, 2020 , Leal et al, 2021 , Policarpo et al, 2021 , Bastos et al, 2020 ) in population restricted to a clinical condition or not, or even in national population studies, ( Santos et al, 2021 , de Souza et al, 2020 , Nascimento et al, 2020 , Marcolino et al, 2021 , Castro et al, 2021 ) but also reported in studies in Latin America, ( Escalera-Antezana et al, 2020 , Araujo et al, 2020 , Elizondo et al, 2021 , Galindo et al, 2021 , Yacobitti et al, 2021 , Ortiz-Prado et al, 2021 ) and in international cohorts ( Pepe et al, 2021 ). Overall, frailty and the high prevalence of comorbidities made the elderly more susceptible to severe infection by COVID-19.…”
Section: Discussionsupporting
confidence: 90%
“…A similar pattern also manifested itself among the older patients, but less pronouncedly, possibly due to the prevalent accumulation of comorbidities among individuals in these strata. Our results confirmed the association of aging with the demand for healthcare resources and COVID-19-related deaths reported in different Brazilian states, ( Sousa et al, 2020 , Macedo et al, 2020 , Cobre et al, 2020 , Escosteguy et al, 2020 , Moura et al, 2020 , Leal et al, 2021 , Policarpo et al, 2021 , Bastos et al, 2020 ) in population restricted to a clinical condition or not, or even in national population studies, ( Santos et al, 2021 , de Souza et al, 2020 , Nascimento et al, 2020 , Marcolino et al, 2021 , Castro et al, 2021 ) but also reported in studies in Latin America, ( Escalera-Antezana et al, 2020 , Araujo et al, 2020 , Elizondo et al, 2021 , Galindo et al, 2021 , Yacobitti et al, 2021 , Ortiz-Prado et al, 2021 ) and in international cohorts ( Pepe et al, 2021 ). Overall, frailty and the high prevalence of comorbidities made the elderly more susceptible to severe infection by COVID-19.…”
Section: Discussionsupporting
confidence: 90%
“…A similar pattern also manifested itself among the older patients, but less pronouncedly, possibly due to the prevalent accumulation of comorbidities among individuals in these strata. Our results confirmed the association of aging with the demand for healthcare resources and COVID-19-related deaths reported in different Brazilian states, (Sousa et al, 2020;Macedo et al, 2020;Cobre et al, 2020;Escosteguy et al, 2020;Moura et al, 2020;Leal et al, 2021;Policarpo et al, 2021;Bastos et al, 2020) in population restricted to a clinical condition or not, or even in national population studies, (Santos et al, 2021;de Souza et al, 2020;Nascimento et al, 2020;Marcolino et al, 2021;Castro et al, 2021) but also reported in studies in Latin America, Araujo et al, 2020;Elizondo et al, 2021;Galindo et al, 2021;Yacobitti et al, 2021;Ortiz-Prado et al, 2021) and in international cohorts (Pepe et al, 2021). Overall, frailty and the high prevalence of comorbidities made the elderly more susceptible to severe infection by COVID-19.…”
Section: Discussionsupporting
confidence: 89%
“…Como descreve Souza et al 16 , a idade avançada pode determinar complicações maiores durante a internação, acarretando em formas mais severas da COVID-19 e evolução para óbito. Nesse mesmo contexto, Policarpo et al 7 apontam para o fato de que a existência de duas ou mais comorbidades aumentam o risco de morte em 2.85 (p=0,02 teste exato de Fisher) em comparação aos indivíduos com apenas uma comorbidade.…”
Section: Resultsunclassified
“…Nos primeiros quatro meses da pandemia, 81,7% das internações por COVID-19 ocorreram em municípios brasileiros com mais de 100 mil habitantes, onde também se registrou o maior número de óbitos 6 . Nesse cenário, idade mais avançada, comorbidade e determinantes sociais têm sido associadas a impactos significativos do número de casos e óbitos, reforçados pelas particularidades de cada região e que contribuem para a disseminação da doença 7 .…”
Section: Introductionunclassified